Greenhouse internet of things temperature intelligent monitoring system - LIU JINGSHU (2017)
The present invention discloses a greenhouse internet of things temperature intelligent monitoring system. The system comprises a temperature sensor connected with a microcontroller which is connected with a communication module, a control execution unit and a power supply, the communication module is in communication connection with a handheld device, an upper computer and a data server, and the control execution unit is connected with an air discharge fan. The greenhouse internet of things temperature intelligent monitoring system is simple in configuration and low in cost, can perform accurate monitoring of the greenhouse temperature data in real time, provide reliable data information for users to make a scientific plantation method and can perform remote automation work management so as to improve the crop output and the economic benefit. 本发明公开了种温室大棚物联网温度智能监控系统，包括：温度传感器，所述温度传感器连接微控制器，所述微控制器分别与通讯模块、控制执行单元及供电电源连接，所述通讯模块分别与手持设备、上位机监控及数据服务器通讯连接，所述控制执行单元连接排气扇。该温室大棚物联网温度智能监控系统架构简单，成本低，能够实时的进行大棚温度数据的精准监控，为使用者提供